AGILE SUPPLY CHAIN DIMENSIONS: APPLICATION IN A SERVICES SUPPLY CHAIN - Martins, A.; Crespo de Carvalho, J.; Menezes, J.; Dias, E.B. (8th International Symposium on Logistics, 2003)
Agility has been a wide discussed concept in the past decade but existing work relates only to manufacturing. The purpose of this paper is to evaluate the ability to apply agility and agile supply chain concepts to the services area. A case study will be used to illustrate the discussion. Agility concepts will be used in the services area. Findings allow affirming that agility and agile supply chain concepts can be used in the chosen services case study. Limitations to the results are identified as well as topic for further research.